Adesão à cerâmica Y-TZP: estudo da deposição de nanofilmes à base de sílica na superfície da Y-TZP - Druck, Carolina Ceolin (2013)
This study in vitro proposed to evaluate the influence of silica-based film coated on the Y-TZP surface on the durability bond strength (BS) between ceramic and resin cement. Eighty Y-TZP blocks (5x5x4 mm) were obtained, included in acrylic resin and were divided into four groups according to the surface treatments treatments (n=20): (TBS) tribochemical silica coating (Cojet, 3M/ESPE), (F-5) 5 nm SiO2 nanofilm and silanization, (F-500) 500 nm SiO2 nanofilm and silanization, and (F-500HF) 500 nm SiO2 nanofilm + HF + silanization. Specimen of composite resin were made with a metal matrix and cemented with resin cement (Relyx ARC) to Y-TZP blocks. Half of the specimens (n=10) of each treatment was tested 24 hours after adhesion (dry), and another half (n=10) will be subjected to the aging (storage for 90 days and 103 thermal cycles). The specimens were submitted to shear test (1min/min). After debonding, the surfaces will be analyzed by optical microscopy and scanning electron microscopy (SEM) to categorize the failure modes and the micro morphology of treated surfaces. Additional analyzes were made in X-ray dispersive energy analysis (EDS). Data were statistically analyzed for Kruskal-Wallis/Mann Whitney (α=0,05) tests. The surface treatment showed significant differences in conditions D (p=0.0001) and A (p=0.0000). In both test conditions , TBS and F-5 promoted the highest bond strength, significantly. Means (SD) for BS data (MPa) were: TBS/D: 10.2 (5.1)AB; F-5/D: 12.0 (3.9)A; F-500/D: 14.9 (4.7)A; F-500HF/D: 4.1 (5.6)B; TBS/A: 9.1 (4.4)a; F-5/A: 7.8 (5.3)a; F-500/A: 0.01 (0.0)b; F-500HF/A: 1.4 (2.3)b. The adhesion to zirconia can be improved if the surface receives a 5 nm layer of SiO2 nanofilm or is subjected to sandblasting with silica particles, followed by silanization.